USING WORD WALL IN TEACHING ENGLISH VOCABULARY AND ITS IMPACT ON THE STUDENTS’ VOCABULARY ACHIEVEMENT - Claudea Imarwiar Efrata; Wahju Bandjarjani (FKIP, Universitas Palangka Raya, 2023)
In learning vocabulary, many media are used. One of the media that can be used is the use of Word Wall. The study aimed to find out the impact of using Word Wall in teaching vocabulary on the students’ vocabulary achievement. The researcher used a quasi-experimental approach with a quantitative approach in this research, which aimed to find out the impact of using Word Wall in teaching vocabulary on the students’ vocabulary achievement. The population was tenth-grade students of a Public Senior High School in West Surabaya and 66 students as research samples taken by cluster random sampling. The results of the calculations showed the impact of using Word Wall in teaching vocabulary on the students’ vocabulary achievement. Researcher measured its effectiveness by using t-test and t-table calculations which showed the t-test result was higher than t-table which was 2,51 > 1,99773. From the increase in scores in the experimental class before the treatment by using Word Wall (Mean = 72,12) and after the treatment (Mean = 90,73). Also from the difference in results between the experimental and admin classes. Furthermore, from the resulting effects, it can be concluded that the language barrier is working in grade 10 public high schools in West Surabaya.